2020
DOI: 10.1016/j.fuproc.2020.106432
|View full text |Cite
|
Sign up to set email alerts
|

From O2/CO2 to O2/H2O combustion: The effect of large steam addition on anthracite ignition, burnout and NOx formation

Abstract: Steam-moderated combustion has been proposed to supress flue gas recycling in oxy-fired units, but the influence of replacing CO2 by H2O has to be deeply studied. In this paper, oxy-fuel combustion of anthracite with large steam addition has been experimentally characterized, and main results are discussed as concerns the influence upon the ignition temperature, the burnout and the NOx formation. The tests have been carried out in an electrically-heated entrained flow reactor for a set of O2/CO2 and O2/H2O/CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…When oxygen concentration is augmented from 21% to 35%, the trend is the same but the evolution is flattened with softer temperature variations. The effect of the steam is attenuated under high O2 concentrations, which is consistent with previous experiences [4,8]. In comparison to the dry O2/CO2 atmospheres, a 40% CO2 replacement by H2O barely affects the ignition temperature, with maximum differences of 6 K.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…When oxygen concentration is augmented from 21% to 35%, the trend is the same but the evolution is flattened with softer temperature variations. The effect of the steam is attenuated under high O2 concentrations, which is consistent with previous experiences [4,8]. In comparison to the dry O2/CO2 atmospheres, a 40% CO2 replacement by H2O barely affects the ignition temperature, with maximum differences of 6 K.…”
Section: Resultssupporting
confidence: 90%
“…Finally, a continuous emission monitoring system provides the flue gas composition at the cold-end section: non-dispersive infrared sensors for CO2, CO SO2, NO, and paramagnetic sensor for O2. A more detailed description of the facility can be found elsewhere [8]. The effect of oxygen concentration (21 and 35% O2) and steam addition (0, 10, 25 and 40%) over the ignition temperature has been experimentally assessed for the two selected coals (SA bituminous and CB sub-bituminous).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it should to be pointed out that the (dW/dt) max in O 2 /H 2 O atmosphere was higher than that in O 2 /N 2 atmosphere at 5% O 2 concentration, which may be attributed to that the (dW/dt) max depended on the combination of oxidation reaction and gasification reaction at low O 2 concentration (i.e., high H 2 O concentration), and gasification reaction occurred accelerated the overall carbon consumption 12 . From all above, we found that with the increasing of O 2 concentration, the contribution of oxidation reaction to carbon consumption rate increased, and this made the proportion of gasification reaction negligible, which is just coinciding with the result of the literatures 34 …”
Section: Resultssupporting
confidence: 86%
“…Energy is produced through the combustion of coal, and nitrogen oxides (NO x ) are the main air pollutants produced in the process. 1 Currently, the main technologies for reducing NO x emissions are flue gas denitrification and low-NO x combustion technology. 2 The technology and equipment required for low-NO x combustion are not yet ready for comprehensive application.…”
Section: Introductionmentioning
confidence: 99%